2011
DOI: 10.1111/j.1530-9290.2010.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria Design of Plastic Recycling Based on Quality Information and Environmental Impacts

Abstract: In this study, we develop a framework for the multicriteria design of plastic recycling based on quality information and environmental impacts for the purpose of supporting collaborative decision making among consumers, municipalities, and recyclers. The subject of this article is the mechanical recycling of postconsumer polyethylene terephthalate (PET) bottles. We present a "quality conversion matrix," which links the quality of recycled PET resin to the quality of waste PET bottles and operational conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Post-consumer material regards the material generated by households or by commercial, industrial or even institutional facilities in their role as end-users of the product. That material can no longer be used for its intended purpose Several articles modeled the economics of recycling from different stakeholders' standpoint, however, there are still a lot of issues to be settled until a consensus to be achieved among them [13]. By examining all the feasible optimal solutions under certain constraints, such as the quality demand and some other criteria such as the environmental impact, a consensus statement or collaborative decision making, among stakeholders could be reached.…”
Section: Economic Approaches On Recyclementioning
confidence: 99%
“…Post-consumer material regards the material generated by households or by commercial, industrial or even institutional facilities in their role as end-users of the product. That material can no longer be used for its intended purpose Several articles modeled the economics of recycling from different stakeholders' standpoint, however, there are still a lot of issues to be settled until a consensus to be achieved among them [13]. By examining all the feasible optimal solutions under certain constraints, such as the quality demand and some other criteria such as the environmental impact, a consensus statement or collaborative decision making, among stakeholders could be reached.…”
Section: Economic Approaches On Recyclementioning
confidence: 99%
“…Concerning data-centric approaches, 5% of the articles used these methods. For example, Caruso et al (1993) used weights defined based on optimisation techniques, whereas El Hanandeh and El-Zein (2010) and Nakatani and Hirao (2011) defined weights using a Monte Carlo simulation. This low frequency of data-centric methods is likely related to the fact that these methods depend on information availability.…”
Section: Weighting Attributionmentioning
confidence: 99%
“…In addition, to use data-centric approaches does not mean to exclude stakeholder involvement. In Nakatani and Hirao (2011), which defines weights by deterministic methods, stakeholders were involved in the decision process by selecting the acceptance limits to each criterion, instead of defining criteria weights.…”
Section: Weighting Attributionmentioning
confidence: 99%
“…A recent U.S. MFA study on PET revealed that in 2016 only about 4.6% of the PET market was recycled in a closed-loop bottle to bottle pathway, while 9.8% of the PET market was recycled in an open-loop pathway (bottles to fiber, sheet, and film applications). MFA can also be coupled with LCA indicators such as greenhouse gas (GHG) emission, energy consumption, and economic indicators associated with different processes. …”
Section: Introduction To Systems Analysis and Plastics In A Circular ...mentioning
confidence: 99%